Trend analysis and age-period-cohort effects on morbidity and mortality of liver cancer from 2010 to 2020 in Guangzhou, China - Wang, Dedong; Hu, Xiangzhi; Xu, Huan; Chen, Yuanyuan; Wang, Suixiang; Lin, Guozhen; Yang, Lei; Chen, Jinbin; Zhang, Lin; Qin, Pengzhe; Wu, Di; Liang, Boheng (Frontiers in Oncology, 2024)
Cross-sectional study, Joinpoint regression (JPR) model and Age-Period-Cohort (APC) model was conducted to analyze the age-standardized incidence rates (ASIR) and age-standardized mortality rates (ASMR) trend of liver cancer in Guangzhou City, China, 2010 to 2020. Age-standardized rates (ASR) of liver cancer in Guangzhou showed an overall decreasing trend. The disparity in risk of morbidity and mortality between the two sexes for liver cancer is increasing. The cohort effect was the most significant among those born in 1965~1970, and the risk of liver cancer incidence and mortality in the total population increased and then decreased with the birth cohort. Compared with the birth cohort born in 1950~1955 (the reference cohort), the risk of liver cancer incidence and mortality in the males born in 1995~2000 decreased by 32% and 41%, respectively, while the risk in the females decreased by 31% and 32%, respectively. Above results indicated that the early detection, prevention, clinical diagnosis, and treatment of liver cancer in Guangzhou have made remarkable achievements in recent years. However, the risk of liver cancer in the elderly and the middle-aged males is still at a high level. Therefore, the publicity of knowledge related to the prevention and treatment of liver cancer among the relevant population groups should be actively carried out to enhance the rate of early diagnosis and treatment of liver cancer and to advocate a healthier lifestyle.